STABILITY IMPROVEMENT OF GRAVITY RETAINING WALL AFTER PLACING BURIED UTILITY RIGID PIPE IN THE BACKFILL (ASEAN Engineering Journal, 2025)
Present study considers a practical possibility where retaining wall construction may take place close to the existing rigid buried utility pipe. Such practical scenario is analyzed numerically using PLAXIS 2D which is a finite element based tool commercially available. Stability trends are captured through a parametric study in which utility buried pipe or tunnel of different diameters i.e. 1.0 m, 1.5m, 2.0m, 2.5m, 3.0m and 3.5m that are placed at different locations in the vertical alignment close to the backside of the retaining wall.  Results of the numerical analysis, i.e., estimation of factor of safety through “strength reduction technique” indicate that keeping other factors constant, such as, backfill geotechnical properties and geometry of the problem statement, the factor of safety (FoS) value is greatly influence by the location and diameter of the Rigid buried utility pipe. Similar trend was captured when the Factor of safety with respect to overturning was estimated with the help of proposed pressure distribution (earth) diagram in active mode behind the gravity retaining wall after placing rigid buried utility pipe on the backside. Further, issue of uncertainty in the geotechnical parameters is considered to estimate the reliability index to estimate the performance in probabilistic framework as well. Combination of numerical analysis, response surface method and first order reliability method eased the calculation with less demand for the computational time.